2022
DOI: 10.1177/09567976221109194
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Soft Materials Draped Over Objects: A Case Study of Intuitive Physics in Perception, Attention, and Memory

Abstract: We typically think of intuitive physics in terms of high-level cognition, but might aspects of physics also be extracted during lower-level visual processing? Might we not only think about physics, but also see it? We explored this using multiple tasks in online adult samples with objects covered by soft materials—as when you see a chair with a blanket draped over it—where you must account for the physical interactions between cloth, gravity, and object. In multiple change-detection experiments ( n = 200), obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…But this trend in vision research goes far beyond the classical domains of core knowledge. Additional work, for example, has suggested that mid-level vision automatically and spontaneously extracts representations of causal history (i.e., of how objects came to look the way that they do; Chen & Scholl, 2016), soft-material intuitive physics (e.g., inferring the shape of objects under cloths; Wong, Bi, Soltani, Yildirim, & Scholl, 2023), and even unfinishedness (as when an object appears not to have ended its movement; Ongchoco, Wong, & Scholl, 2023). But competence involving such seemingly sophisticated domains is nowhere to be found in most characterizations of core knowledge.…”
Section: Progress: Sophisticated Seeing!mentioning
confidence: 99%
“…But this trend in vision research goes far beyond the classical domains of core knowledge. Additional work, for example, has suggested that mid-level vision automatically and spontaneously extracts representations of causal history (i.e., of how objects came to look the way that they do; Chen & Scholl, 2016), soft-material intuitive physics (e.g., inferring the shape of objects under cloths; Wong, Bi, Soltani, Yildirim, & Scholl, 2023), and even unfinishedness (as when an object appears not to have ended its movement; Ongchoco, Wong, & Scholl, 2023). But competence involving such seemingly sophisticated domains is nowhere to be found in most characterizations of core knowledge.…”
Section: Progress: Sophisticated Seeing!mentioning
confidence: 99%
“…But this trend in vision research goes far beyond the classical domains of core knowledge. Additional work, for example, has suggested that mid-level vision automatically and spontaneously extracts representations of causal history (i.e., of how objects came to look the way that they do; Chen & Scholl, 2016), soft-material intuitive physics (e.g., inferring the shape of objects under cloths; Wong, Bi, Soltani, Yildirim, & Scholl, 2023), and even unfinishedness (as when an object appears not to have ended its movement; Ongchoco, Wong, & Scholl, 2023). But competence involving such seemingly sophisticated domains is nowhere to be found in most characterizations of core knowledge.…”
Section: Progress: Sophisticated Seeing!mentioning
confidence: 99%
“…On the other hand, WBK also provides several additional arguments against this view, which seem less compelling. Spelke suggests that some aspects of core knowledge cannot have perceptual origins because (a) core knowledge representations are abstract (p. xxi)but many aspects of mid-level vision also abstract over many surface variables (Scholl, 2007); (b) perception involves "detectable surfaces" rather than "the entities that those surfaces belong to" (p. 198)but recent work in mid-level vision argues for exactly the opposite view (Wong et al, 2023); and (c) core knowledge representations have a time-course that transcends momentary perception (p. 78)but at least some object-file representations in mid-level vision have been shown to persist throughout interruptions for at least 8 seconds, and possibly much longer (a result that was also explicitly motivated by connections to infant cognition; Noles, Scholl, & Mitroff, 2005). Some of the most recent discussions of core knowledge also still seem to veer away from the possibility of substantive connections to mid-level vision in other ways.…”
Section: The State Of the Artmentioning
confidence: 99%
“…When physical constraints are violated, it can lead to the perception of animated, self-generated motion (Parovel 2023). Additionally, there is evidence suggesting that certain relatively complex relational properties of physical events are processed early by the visual system, preceding the involvement of higher-level cognitive processes (Hafri and Firestone 2021;Little and Firestone 2021;Wong et al 2023).…”
Section: A Brief Historical Overview Of the Study Of Intuitive Physicsmentioning
confidence: 99%